Linking internalizing symptoms and dyadic adjustment during pregnancy among Portuguese first-time parents: The mediating role of dyadic coping - Pereira, Marco (2020)
This study examined the mediating role of dyadic coping (DC) in the association between internalizing symptoms and dyadic adjustment in a sample of 184 couples expecting their first child. Each partner completed self-report questionnaires assessing symptoms of depression and anxiety, dyadic adjustment and DC during the second trimester of pregnancy. An extension of the actor-partner interdependence model for testing direct and indirect effects was used. Compared to men, women presented higher levels of internalizing symptoms and dyadic adjustment and engaged more in DC by self. Significant indirect effects of internalizing symptoms on dyadic adjustment via common DC and DC by one’s partner were found. Specifically, higher internalizing symptoms were associated with lower common DC and DC by one’s partner, which, in turn, were associated with lower dyadic adjustment. This mediation occurred either within person as well as across partners and occurred similarly for women and men. These results suggest that primiparous couples may benefit from DC-enhancing interventions, such as the cognitive-behavioral couple-based programs Couples Coping Enhancement Training (CCET) and Coping-Oriented Couple Therapy (COCT), to assist them in responding sensitively to their partners’ psychological symptoms, which may have a positive effect on marital adjustment.